Analisa Sistem Informasi Administrasi Laboratorium pada Rumah Sakit Kanker Dharmais - Ardiansyah Ardiansyah; Ahmad Taufik (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to conduct an in-depth analysis of the laboratory administration application system used at Dharmais Cancer Hospital. The research focuses on evaluating the system’s functionality, performance, and integration with other hospital systems to assess its effectiveness in supporting laboratory administrative operations. The research method employed a quantitative survey using a questionnaire that measured five key dimensions of service quality: Tangibles (physical appearance and facilities), Reliability, Responsiveness, Assurance, and Empathy (sensitivity to user needs) The findings indicate that the system’s functionality is categorized as